The major tectonic boundaries of the Northern Red Sea rift, Egypt derived from geophysical data analysis - SALEH, Salah; PAMUKҪU Oya; BRIMICH, Ladislav (Contributions to Geophysics and Geodesy, 2017)
In the present study, we have attempted to map the plate boundary between Arabia and Africa at the Northern Red Sea rift region including the Suez rift, Gulf of Aqaba-Dead Sea transform and southeastern Mediterranean region by using gravity data analysis. In the boundary analysis method which was used; low-pass filtered gravity anomalies of the Northern Red Sea rift region were computed. Different crustal types and thicknesses, sediment thicknesses and different heat flow anomalies were evaluated. According to the results, there are six subzones (crustal blocks) separated from each other by tectonic plate boundaries and/or lineaments. It seems that these tectonic boundaries reveal complex structural lineaments, which are mostly influenced by a predominant set of NNW–SSE to NW–SE trending lineaments bordering the Red Sea and Suez rift regions. On the other side, the E–W and N–S to NNE–SSW trended lineaments bordering the South-eastern Mediterranean, Northern Sinai and Aqaba-Dead Sea transform regions, respectively. The analysis of the low pass filtered Bouguer anomaly maps reveals that the positive regional anomaly over both the Red Sea rift and South-eastern Mediterranean basin subzones are considered to be caused by the high density of the oceanic crust and/or the anomalous upper mantle structures beneath these regions whereas, the broad medium anomalies along the western half of Central Sinai with the Suez rift and the Eastern Desert subzones are attributed to low-density sediments of the Suez rift and/or the thick upper continental crustal thickness below these zones. There are observable negative anomalies over the Northern Arabia subzone, particularly in the areas covered by Cenozoic volcanics. These negative anomalies may be attributed to both the low densities of the surface volcanics and/or to a very thick upper continental crust.